2007
DOI: 10.1088/1742-6596/88/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the dynamics of laser-cluster interaction

Abstract: Abstract. We study the interaction of an intense (I 10 15 Wcm −2 ) femtosecond laser pulse with a large (N > 10000 atoms) rare-gas cluster. The simulations are based on a mean-field classical transport approach. The electronic dynamics during the interaction with the laser are discussed in more detail. In particular we point out the difference in behavior between the fast electrons and the collectively moving slow electrons and try to shed light on the acceleration mechanisms behind the high energy tail of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…We found that the Xe K-shell X-ray photon number increases with increasing cluster radius from 8 to 12 nm, and then saturates at cluster radii between 12 and 17 nm. This result is similar to the result obtained by Deiss (2009) that an Ar cluster radius on the order of 10 nm is optimum for Ar K-shell X-ray generation.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We found that the Xe K-shell X-ray photon number increases with increasing cluster radius from 8 to 12 nm, and then saturates at cluster radii between 12 and 17 nm. This result is similar to the result obtained by Deiss (2009) that an Ar cluster radius on the order of 10 nm is optimum for Ar K-shell X-ray generation.…”
Section: Resultssupporting
confidence: 91%
“…A similar cluster radius dependence was found for Ar K-shell X-ray generation simulated by Deiss (2009). Laser-cluster interaction was simulated with a mean-field classical transport approach.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation